Additive for rubber compounds and method for producing same

JP2024510922A5Active Publication Date: 2025-02-27MCD TECHNOLOGIES S A RL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023553006
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-05
Filing Date
2022-02-21
Publication Date
2025-02-27
Estimated Expiration
2042-02-21

AI Technical Summary

Technical Problem

Existing methods for incorporating carbon nanotubes into rubber compounds face challenges in achieving uniform distribution and preventing re-agglomeration, which adversely affects electrical conductivity and mechanical properties, particularly when using high viscosity viscoelastic components like rubber.

Method used

A rubber additive comprising 1-20% carbon nanotubes, 90-95% high viscosity organic rubber, and a low molecular weight dispersion medium that dissolves the high viscosity rubber, preventing carbon nanotube agglomeration during mixing and ensuring uniform dispersion.

Benefits of technology

The additive significantly enhances electrical conductivity, mechanical properties, and thermal conductivity of rubber, while maintaining mechanical strength and reducing the presence of black marks, with improved tensile strength, abrasion resistance, and dynamic properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an additive for improving electrical conductivity and physical and mechanical properties of rubber compounds, including modulus, tensile strength, tear resistance and abrasion resistance of composite elastomeric materials (rubbers), among others. The present invention proposes an additive containing 1-20% by weight of carbon nanotubes, 3-90% by weight of high viscosity organic rubber, and 8-95% by weight of low molecular weight organic dispersion medium. The present invention also proposes a method for producing the additive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to additives for improving electrical conductivity and physical and mechanical properties of rubber compounds, including modulus, tensile strength, tear resistance and abrasion resistance, among others, for composite elastomeric materials (rubbers), and composite elastomeric materials (rubbers). [Background technology]

[0002] Many fillers of various chemistries and morphologies are known that, when added to rubber compounds, enhance the mechanical properties of the rubber, i.e., modulus, tensile strength, tear resistance, etc. "Rubber compound" herein refers to rubber before curing or a mixture based on two or more rubbers. "Rubber" herein refers to the product of curing a rubber compound. Some of these fillers enhance the electrical conductivity of the rubber, the most widespread of such fillers being various types of carbon black. The drawback of using carbon black is that large amounts of carbon black (e.g., more than 30 parts per 100 parts of rubber) are required to obtain the required electrical conductivity. Adding such significant amounts of carbon black has a detrimental effect on certain physical and mechanical properties, such as abrasion resistance. Carbon nanotubes are promising fillers that can enhance the electrical conductivity and physical and mechanical properties of rubber when added in relatively small amounts, due to the large length-to-diameter ratio typical of their morphology. Among carbon nanotubes, nanotubes with the fewest number of walls (double-walled or single-walled carbon nanotubes) are the most preferred, since they have the largest length-to-diameter ratio and the largest specific surface area. By adding a fairly small amount of single-walled carbon nanotubes, such as 0.3% by weight, to rubber, 4 Experimental data is available (e.g., Russian Patent No. 2731635, IPC: B60C11 / 00) showing that rubber volume resistivities of less than ohm·m can be obtained.

[0003] The addition of carbon nanotubes, especially single-walled or double-walled carbon nanotubes, to composites poses serious technical challenges. To achieve the technical result, i.e. to improve the electrical conductivity and physical and mechanical properties of the rubber, one must ensure the dispersion of the entangled agglomerates of carbon nanotubes to the smallest possible size, preferably to bundles of carbon nanotubes, without damaging or destroying the carbon nanotubes, and to distribute the carbon nanotubes uniformly throughout the bulk of the rubber compound. The addition of carbon nanotubes to composites is very challenging for any material, but for rubber compounds it is further complicated by the viscoelastic properties of the rubber polymer in combination with its high viscosity.

[0004] One approach disclosed for the dispersion of nano-sized additives in rubber-containing compounds utilizes pre-dispersion in an aqueous rubber dispersion, i.e., latex. According to EP 2436720, 07 / 23 / 2014, IPC:С08J3 / 00, C08J3 / 215, C08J3 / 22, carbon nanotubes are first dispersed in the aqueous phase using ultrasound, then the polymer latex is added, and then coagulation takes place. The resulting masterbatch is further processed (dried). A drawback of this method is that a significant amount of dispersant remains in the resulting masterbatch, which has a detrimental effect on the rubber and the parts made therefrom (such as reducing the elasticity and / or strength of the rubber). Furthermore, when carrying out the manufacturing method disclosed in EP 2436720, a large amount of water remains in the masterbatch after coagulation, which requires costly drying.

[0005] Another publication [Russian Patent No. 2619782, 05 / 18 / 2017, IPC: С01B31 / 00, С08J3 / 22, C08J3 / 26, B82Y30 / 00, B29B7 / 34, B29B7 / 56] discloses a method for preparing a masterbatch containing carbon nanotubes in a high-viscosity rubber, which includes mixing the nanotubes with at least one rubber latex, heating to 100°C-200°C, evaporating the water, and then dispersing them on a three-roll mill, in which single-walled, multi-walled or double-walled carbon nanotubes are used as nanoparticles, the masterbatch containing carbon nanotubes is transferred along the central roll to the gap between the central roll and the delivery roll, then dispersed therein, and then removed from the delivery roll, the gap size being 5-120 μm, and the gap size is reduced by more than 1.5 times each time the gap is passed through. The evaporation of water is preferably carried out in a mixing unit such as an extruder, an internal mixer or a press mixer. The masterbatch produced according to Russian Patent No. 2619782 disperses carbon nanotubes to an aggregate size of less than 10 μm in a high-viscosity rubber latex having a water content of less than 10% by weight, preferably less than 1% by weight. The disadvantage of this method is the complexity, duration and energy consumption of the evaporation stage in the course of mixing, the example provided requires more than 20 minutes of mixing in an internal mixer. Such long processing in a rubber mixer can cause substantial damage to both the rubber and the carbon nanotubes. Due to the high viscosity of the rubber, processing of the mixture of carbon nanotubes and latex after water removal in a three-roll mill also requires high torque, so that conventional three-roll mills cannot be used for this purpose and special equipment is required.

[0006] Another approach to the pre-dispersion of nano-sized additives in rubber containing compounds is based on the pre-dispersion of carbon nanotubes in a specific liquid dispersion medium with low elasticity. Such dispersion is more efficient than dispersion in high viscosity and viscoelastic rubbers or their latexes. On the other hand, the mixing of composites with additives that are dispersions containing nanotubes in this liquid dispersion medium is more efficient than powders of non-dispersed carbon nanotubes, providing a more uniform distribution of nanotubes in the form of individual nanotubes or their agglomerates of small size. Dispersion of carbon nanotubes in such a dispersion medium can be achieved by a wide range of techniques, including processing by ultrasound, bead mills, high pressure dispersers, three-roll mills, and other known methods for dispersion and mixing. However, an obvious drawback of using CNT dispersions in liquid media is the introduction of a significant amount of dispersion medium into the composite.

[0007] This drawback is overcome in Russian Patent Specification No. 2654959, 05 / 23 / 2018, IPC:С01B32 / 174, B82B1 / 00, B82B3 / 00, B82Y40 / 00 which provides an ultra-concentrate of carbon nanotubes, which is a dispersion comprising carbon nanotubes as dispersed phase and a dispersion medium, the dispersion being obtained by mixing the carbon nanotubes with the dispersion medium, the dispersion comprising at least 2% by weight of carbon nanotubes, and being obtained by mechanically processing the mixture of carbon nanotubes and the dispersion medium to a maximum size of carbon nanotube agglomerates not exceeding 50 μm, the dispersion medium being a material having a contact angle with highly oriented pyrolytic graphite of less than 120°.

[0008] By using such "ultraconcentrates", i.e. highly concentrated CNT dispersions, the amount of dispersing medium introduced can be reduced to a relatively small amount (less than 49 of the mass of the CNTs introduced). When one of the components of the composite (e.g. plasticizer or epoxy-based agent, or other components) is used, this allows adding substantial amounts of carbon nanotubes predispersed in the ultraconcentrate, i.e. up to 1 wt. % or more, to the composite without the need to remove the dispersing medium from the composite.

[0009] For rubber compounds, a method is known to prepare a masterbatch containing carbon nanotubes in liquid rubber according to EP 2607407, 08 / 20 / 2014, IPC: C08J3 / 22, C08K3 / 04, C08J5 / 00, C08J3 / 20, C08L9 / 02, C08L21 / 00, by dispersing them on a three-roll mill, which is adopted as a prototype of the present invention. The method of the cited publication makes it possible to achieve a small size of carbon nanotube agglomerates in the masterbatch by dispersing 5-50% by weight of carbon nanotubes in a dispersing medium containing liquid rubber with a mass average molecular weight (MW) of 500 g / mol to 200 kg / mol (preferably 500 g / mol to 100 kg / mol, most preferably 500 g / mol to 20 kg / mol).

[0010] A common feature of the method for preparing the super concentrate of RU2654959 and the master batch of EP2607407 is that the main technical result of the cited invention is a good dispersion of carbon nanotubes in the super concentrate and in the master batch: the absence of large agglomerates of carbon nanotubes larger than 50 μm in the super concentrate of RU2654959, while EP2607407 mentions the absence of agglomerates larger than 130 μm, preferably larger than 50 μm, more preferably larger than 10 μm in the master batch. A common drawback of the super concentrate of RU2654959 and the master batch of EP2607407 is that, despite the absence of large agglomerates of carbon nanotubes in the super concentrate or in the master batch, their addition to a composite based on a highly viscous viscoelastic component such as rubber causes re-agglomeration of the carbon nanotubes, and thus a uniform distribution and good dispersion of the carbon nanotubes in the final composite is not achieved. The process of carbon nanotube re-agglomeration is more pronounced for double-walled and single-walled carbon nanotubes, which can spontaneously bundle under the influence of van der Waals forces (π-π interactions). Because the disclosure and examples of EP 2607407 are limited to masterbatches containing multi-walled carbon nanotubes, the inventors did not discover this drawback of their proposed method, which becomes apparent when using single-walled carbon nanotubes.

[0011] There are two options for carrier fluids for super concentrates or masterbatches: (1) a carrier fluid that is soluble in one of the main components of the composite (such as rubber), or (2) a carrier fluid that is insoluble in the main component of the composite.

[0012] (1) When using a dispersing medium that is soluble in one of the main components of the composite, in the process of mixing the super concentrate of RU 2654959 or the master batch of EP 2607407 with a rubber compound containing high viscosity rubber, the dispersing medium dissolves in the rubber compound many times faster than the super concentrate or master batch is mixed with the rubber compound, resulting in the absorption of the dispersing medium into the rubber compound with the formation of large agglomerates from the carbon nanotubes. As a result, the carbon nanotubes in the composite are well distributed but poorly dispersed.

[0013] (2) When an insoluble carrier is used for one of the main components of the composite, in the process of mixing the ultra concentrate of RU2654959 and EP2607407 with a composition containing a high-viscosity viscoelastic component, the low-viscosity ultra concentrate or master batch behaves like a lubricant (compared to rubber), resulting in a poor mixing quality of the rubber compound, and finally the formation of an emulsion of the ultra concentrate or master batch in the rubber compound, leading to poor distribution of the carbon nanotubes in the rubber compound. As the examples provided below show, the addition of the ultra concentrate of RU2654959 or the master batch of EP2607407 to the rubber compound results in a low effect of the introduced carbon nanotubes on the physical and mechanical properties and electrical conductivity, and in some cases even a decrease in the physical and mechanical properties.

[0014] A significant drawback of the method of preparing masterbatches of EP 2607407 is that the subsequent addition of such masterbatches to rubber compounds introduces a large amount of liquid rubber into the rubber compound together with the carbon nanotubes, i.e., the rubber of relatively low molecular weight. For example, if a styrene butadiene liquid rubber has an average molecular weight (MW) of 1000 Da, this means that the styrene and butadiene monomer units are present on average only six times each in the rubber molecules, but in a significant proportion of the rubber molecules only five times each or less. The addition of significant amounts of rubber oligomers alters the kinetics of the curing process, the post-curing structure of the polymer, and has a detrimental effect on the physical and mechanical properties of the rubber. This drawback is an inherent feature of the masterbatches produced by the method of EP 2607407, which is caused by the use of liquid rubber as a dispersing medium rather than, for example, plasticizing mineral oil or other low molecular weight solvents that do not modify the molecular weight distribution of the rubber polymer when introduced into the rubber.

[0015] In view of the above, the technical objectives are to provide an additive for rubber compounds which contains carbon nanotubes and improves both the electrical conductivity and the physical and mechanical properties of the rubber; to provide a method for producing an additive for rubber compounds which contains carbon nanotubes and improves both the electrical conductivity and the physical and mechanical properties of the rubber; to provide a method for producing rubber having improved electrical conductivity and physical and mechanical properties; and to provide a rubber having improved electrical conductivity and physical and mechanical properties which contains carbon nanotubes. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] Russian Patent No. 2731635 [Patent Document 2] European Patent No. 2436720 [Patent Document 3] Russian Patent No. 2619782 [Patent Document 4] Russian Patent No. 2654959 [Patent Document 5] European Patent No. 2607407 Summary of the Invention

[0017] In one aspect, the present invention provides an additive for a rubber compound for improving the electrical conductivity and physical and mechanical properties of the rubber, the additive comprising carbon nanotubes, 1 to 20% by weight of carbon nanotubes, 3 to 90% by weight of a high-viscosity organic rubber (R), and 8 to 95% by weight of a low-molecular-weight organic dispersion medium capable of dissolving the high-viscosity organic rubber (R).

[0018] The presence of high viscosity rubber in the additive prevents aggregation of carbon nanotubes in the process of dissolving the dispersion medium in the rubber compound when the additive and the rubber compound are mixed.

[0019] The technical result of using such additives in rubber compounds is an increase in the electrical conductivity of the rubber, i.e. a decrease in the volume resistivity of the rubber, as well as an improvement in the physical and mechanical properties, including the rubber modulus according to standard [ISO 37:2017.Rubber,vulcanized or thermoplastic-Determination of tensile stress-strain properties], the rubber tear resistance according to standard [ISO 34:1979.Rubber,vulcanized-Determination of tear strength(trouser,angle and crescent test pieces)], and the rubber hardness according to standard [ISO 7619-1:2010 Rubber,vulcanized or thermoplastic-Determination of indentation hardness-Part 1:Durometer method(Shore hardness)].

[0020] Additional technical results achieved by using such additives may be, but not in all cases of their use, increased rubber tensile strength, increased rubber thermal conductivity, increased rubber abrasion resistance, improved dynamic properties of rubber, including increased storage modulus, increased loss factor (mechanical loss tangent) of rubber at 0°C and 20°C. Additional technical results of using the provided additives for rubber compounds, compared to other conductive additives such as carbon black, may be lighter colored rubber, the possibility of producing colored rubber when suitable pigments are introduced, and the possibility of producing rubber that does not leave black marks on surfaces it comes into contact with.

[0021] "High viscosity organic rubber" means a rubber with a Mooney viscosity ML of more than 20 at 100°C. (1+4) This refers to synthetic or natural saturated or unsaturated rubber having a mass average molecular weight (M w) can reach 1000 kg / mol (1 million Daltons) or more. Such rubbers are sometimes called "solid" rubbers, not to imply crystallinity, but rather to contrast with "liquid rubbers", i.e., oligomers with lower average molecular weight and lower viscosity. As the examples of the present invention show, the presence of high viscosity or "solid" organic rubbers in the additive ensures the formation of a significant amount of bound rubber therein, which in turn promotes good distribution and dispersion of the carbon nanotubes in the rubber compound. Synthetic or natural saturated or unsaturated rubbers can be used as high viscosity organic rubbers (R), including, but not limited to, natural or synthetic isoprene rubber, styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, butadiene rubber, butyl rubber, halobutyl rubber, ethylene propylene rubber, ethylene norbornene or ethylene propylene diene rubber with 1,4-hexadiene or dicyclopentadiene as the third monomer, propylene oxide rubber, acrylate rubber, carboxylate rubber, chloroprene rubber, fluoroelastomer, polysulfide rubber, epichlorohydrin rubber, urethane rubber, chlorosulfonated rubber, or combinations thereof. As high viscosity rubbers (R), i.e. synthetic rubbers into which organic plasticizers (oils) have been introduced during the manufacturing stage, oil extended rubbers can be used. In contrast to high viscosity "solid" organic rubbers, the presence of low viscosity "liquid" rubbers in the additive is undesirable and should preferably be avoided for the reasons mentioned above.

[0022] High viscosity organic rubber (R) has a viscosity of ML at 100°C. (1+4) It is preferable that the rubber viscosity exceeds 20 Mooney Units (MU) (determination of rubber viscosity should be made in accordance with Russian standard GOST R 54552-2011 Rubbers and Rubber Compounds. Determination of Viscosity, Stress Relaxation and Pre-Vulcanization Characteristics by Mooney Viscometer, or the equivalent standard ASTM D 1646-2015). In certain applications, high viscosity organic rubbers have a viscosity ML of more than 40 Mooney Units at 100°C. (1+4)In other applications, the high viscosity organic rubber preferably has a viscosity ML of greater than 60 Mooney units at 100° C. (1+4) It is preferred that the compound has the formula:

[0023] "Low molecular weight dispersion medium" refers to a liquid low molecular weight organic compound having a molecular weight of less than 900 g / mol, or a solution of a plurality of low molecular weight organic compounds (i.e. compounds having a molecular weight of less than 900 g / mol). From the standpoint of processability, both in the manufacture of the additive and in its subsequent use, the flash point of the dispersion medium is preferably greater than 100°C, while the dynamic viscosity of the dispersion medium at temperatures below 100°C is preferably less than 0.1 Pa·s.

[0024] The carrier fluid may be a liquid phase comprising a mineral oil, such as naphthenic, paraffinic, or aromatic oils. In certain applications, the low molecular weight carrier fluid is preferably a mineral oil or other mineral oil of similar composition to the oils used to extend organic synthetic rubbers (e.g., the TDAE class aromatic oils used to extend styrene butadiene rubber). For such applications, the low molecular weight carrier fluid is preferably a mineral oil having a flash point above 200°C and a kinematic viscosity at 100°C of less than 0.1 St.

[0025] In certain applications, the low molecular weight dispersion medium is preferably a polar solvent with a dielectric constant greater than 5 at 25°C. The high polarity of the dispersion medium promotes good dispersion of the carbon nanotubes in some cases. Most preferably, the dielectric constant of the dispersion medium is greater than 40 at 25°C. For example, the dispersion medium can include, but is not limited to, greater than 10% by weight of propylene carbonate, or 1,2-butylene carbonate, or 2,3-butylene carbonate, or mixtures thereof. In other applications, N,N-dimethyl lactamide and / or N-formyl morpholine, and / or other polar organic compounds can be used as components of the dispersion medium.

[0026] It should be noted that technical results can also be achieved using a less polar carrier fluid. In certain applications, the carrier fluid preferably comprises an ester or mixture of esters of an aliphatic alcohol with at least 20% by weight of an acid selected from phthalic acid, or terephthalic acid, or sebacic acid, or adipic acid, or cyclohexanedicarboxylic acid, such as, but not limited to, dibutyl phthalate, dioctyl sebacate, dioctyl adipate, cyclohexanoyl cyclohexanoate. In certain other cases, polar carrier fluids are undesirable as they can have a detrimental effect on the interaction of other components of the rubber compound.

[0027] "Carbon nanotube" refers to a cylindrical carbon nanostructure with a diameter of 0.7 nm to 50 nm, consisting of one or more carbon (graphene) layers. Single-walled carbon nanotubes and / or double-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used in the rubber compound of the present invention. The surface of the carbon nanotube can be modified with organic groups, such as functional groups such as carboxy or hydroxy, or those containing one or more amino groups and / or sulfoxy groups and / or epoxy groups and / or peroxy groups and / or other groups, but are not limited to the listed examples. The structure of the carbon nanotube can include heteroatoms, such as nitrogen atoms. Single-walled carbon nanotubes with a diameter of more than 0.7 nm and less than 6 nm can be used as carbon nanotubes.

[0028] It is known that single-walled and double-walled nanotubes can be bundled due to van der Waals forces (π-π interactions). As the nanotubes are bundled, both the diameter and length of the bundle increase, and as the number of nanotubes in the bundle increases, the length / diameter ratio of the nanotube bundle increases. It is also known that the higher the length / diameter ratio of the particles in the conductive filler, the lower the minimum concentration of conductive filler that ensures the presence of connected conductive clusters (percolation threshold). Therefore, the number of nanotubes in the bundle, and therefore the diameter of the nanotube bundle in the final rubber compound, is preferably as large as possible, for example greater than 300 nm, preferably greater than 1 μm, preferably greater than 3 μm, in order to achieve a lower percolation threshold.

[0029] On the other hand, the presence of multiple thin nanotube bundles in a material is also desirable to ensure the homogeneity of the material, to maintain its physical and mechanical properties (including strength and wear resistance), and to reduce the contact resistance of the material. Therefore, additives in which the nanotubes are combined into bundles with a wide bundle diameter distribution, such as 10 nm to 500 nm, or more preferably 5 nm to 1 μm, or more preferably 3 nm to 3 μm, are preferred.

[0030] Multi-walled nanotubes are usually combined into entangled aggregates, but not into bundles. Entangled nanotube aggregates in the material are undesirable. Preferably, greater than 25% by weight of the carbon nanotubes in the additive are double-walled or single-walled, and most preferably greater than 50% by weight of the carbon nanotubes are single-walled. A feature that sets single-walled carbon nanotubes apart from other carbon allotropes is their unique Raman spectrum at about 1330 cm. -1 Compared to the D band, the maximum is about 1580 cm -1The higher the intensity ratio of the G / D band in the Raman spectrum, the better. The carbon nanotubes in the additive are preferably characterized by an intensity ratio of the G / D band in the Raman spectrum at 532 nm of more than 10. More preferably, the carbon nanotubes in the additive are characterized by an intensity ratio of the G / D band in the Raman spectrum at 532 nm of more than 40. Most preferably, the carbon nanotubes in the additive are characterized by an intensity ratio of the G / D band in the Raman spectrum at 532 nm of more than 60. However, it should be noted that in certain applications, technical results can also be achieved when the content of single-walled carbon nanotubes in the additive is low and thus the intensity ratio of the G / D band is low.

[0031] When the additive of the present invention is mixed with a rubber compound, a uniform network of well-dispersed carbon nanotubes and their bundles is formed in the rubber compound, which increases the electrical conductivity, elastic modulus, tear resistance and hardness of the rubber. To achieve this technical result, it is necessary to disperse the carbon nanotubes in a carrier medium compatible with the target rubber compound, and to have a high viscosity rubber present in the additive, as well as to have the carbon nanotube concentrate contain the high viscosity rubber. This prevents the carbon nanotubes from re-agglomerating during the mixing of the rubber compound, maintains a high degree of dispersion of the carbon nanotubes and ensures a uniform distribution in the final composite. A fraction of the high viscosity rubber in the additive preferably binds to the carbon nanotubes, forming a layer of bound rubber around the carbon nanotubes. Hereinafter, the conventional term "bound rubber" (BdR) as used in rubber technology refers to the rubber fraction that cannot be extracted from an uncured filled rubber compound in a suitable solvent, i.e. a solvent in which the solubility of the rubber is not limited (see, for example, JL Leblanc, Elastomer-Filler Interactions and the Rheology of Filled Rubber Compounds, Journal of Applied Polymer Science, Vol. 78, 1541-1550 (2000)).

[0032] The residue (tail) after extraction of the rubber from the additive in a large amount (e.g. more than 100-fold excess) of organic solvent forming an unlimited series of organic rubber (R) solutions for a long period (e.g. more than 7 days) preferably comprises more than 20% by weight of rubber, i.e. the additive preferably comprises bound rubber, the ratio of the mass fraction of carbon nanotubes and the rubber bound to them being preferably less than 4. The molecules of the polymer in the bound rubber can be chemically bound to the functional groups on the surface of the carbon nanotubes, but this is not essential, and the rubber interaction with the filler, and in particular with the carbon nanotubes, can be due to van der Waals forces.

[0033] In addition to the carbon nanotubes, the carrier fluid, and the rubber, the additive of the present invention may contain other components such as particles of metals from Groups 8 to 11 of the Periodic Table, such as iron, cobalt, nickel, ruthenium, rhodium, palladium, iridium, platinum, copper, silver, gold, or alloys thereof, but are not limited to the listed examples. Metal particles may be introduced into the additive along with the carbon nanotubes as impurities due to the method of producing the carbon nanotubes. Metal particles or other components may be intentionally introduced into the additive to modify one or more properties of the rubber compound.

[0034] Variations in the carbon nanotube content, rubber content, and the nature of the carrier medium may alter certain physical and chemical properties of the additive, such as its viscosity and electrical conductivity. In certain applications, the additive should preferably not differ significantly in viscosity from the rubber compound, for example within the range of 5 to 90 Mooney units at a temperature of 100°C, in order to ensure better mixing with the rubber compound. In certain other applications, the additive may be less viscous. In this case, its viscosity is preferably characterized by the needle penetration depth at 25°C for 5 seconds under a specified load of 100 g according to Russian standard GOST-11501-78 (or equivalent standards DIN EN1426:2015, ASTM D5). In addition to characterizing the viscosity of the additive, this property also describes the uniformity of the dispersion and distribution of the carbon nanotubes in the carrier medium, with the needle penetration depth increasing significantly in the case of a non-uniform additive. The needle penetration depth is preferably less than 20 mm (200 penetration units equal to 0.1 mm), most preferably less than 15 mm, and in certain applications the penetration depth is preferably less than 10 mm (100 penetration units equal to 0.1 mm).

[0035] Furthermore, in certain applications, to ensure a better effect on the electrical conductivity of the final rubber compound, the additive should preferably have a conductivity of at least 0.5 S / m, i.e. its volume resistivity at 25°C is equal to or less than 2 ohm·m, although in some other applications a lower conductivity of the additive may be sufficient.

[0036] The present invention also provides a method for the preparation of the additive defined above, comprising the following successive steps: step (I) - dissolving the high viscosity rubber (R) in said dispersion medium, and step (II) - dispersing carbon nanotubes in the solution of step (I). The solution of step (I) can be a true or colloidal solution of rubber in the dispersion medium. Even if a true rubber solution is prepared in the dispersion medium in step (I), the rubber interacts with the carbon nanotubes after step (II) to form a bound rubber phase that is no longer soluble in the dispersion medium or when extracted with an organic solvent. The amount of this phase is preferably more than 25% by weight of the amount of carbon nanotubes in the additive. The carbon nanotubes can be dispersed in the solution of rubber in the dispersion medium by using one of the known methods for slurry dispersion and homogenization, including but not limited to ball mills, planetary mills, twin screw homogenizers, rotor stator homogenizers, three-roll mills, roller mills with four or more rolls, internal rubber mixers with various rotor geometries, two-roll rubber mills.

[0037] Since carbon nanotubes are a powder that poses a potential danger to personnel and equipment, an additional step of pre-wetting and mixing the carbon nanotubes in the dispersion medium, or in one of the components of the dispersion medium, or in the rubber solution in the dispersion medium, is preferably carried out between steps (I) and (II). This pre-wetting and mixing can be carried out in any known type of mixer, including, but not limited to, single- or double-shaft mixers, planetary mixers, kneaders, overhead stirrers with various impeller geometries, and rotary mixers. The quality of the mixing in the pre-wetting and mixing step does not play a distinct role, since the main objective of this process step is wetting of the carbon nanotubes, easy dosing, and lack of dust during the subsequent dispersion in step (II).

[0038] In some cases, it is advantageous to further include a step of mixing the resulting paste containing carbon nanotubes, a dispersion medium, and a high-viscosity organic rubber (R) with a high-viscosity organic rubber (R2) after step (II). The high-viscosity organic rubber (R2) may have different chemical properties and physical and chemical properties from the high-viscosity organic rubber (R), but a rubber (R) similar to the rubber (R2) may be used. The resulting mixture may also be used as an additive in rubber compounds to increase electrical conductivity and physical and mechanical properties. The ratio of the weight of the rubber (R2) to the weight of the slurry after step (II) is preferably 5 or less. The additional mixing of the slurry containing carbon nanotubes, a dispersion medium, and a high-viscosity organic rubber (R) with the high-viscosity organic rubber (R2) can be carried out using any known device for rubber mixing, such as an internal mixer with tangential rotors, or an internal mixer with intermeshing rotors, or a two-roll rubber mill, but is not limited to the listed examples.

[0039] The present invention also provides a method for producing rubber with enhanced electrical conductivity and physical and mechanical properties, comprising the step of adding an additive comprising carbon nanotubes as defined above to a rubber compound. "Rubber compound" refers to rubber before curing or a mixture based on two or more rubbers. Adding the additive to the rubber compound can be carried out as a separate process step or can be combined with adding fillers and / or plasticizers and / or antioxidants and / or silane coupling agents and / or curing agents and / or cure accelerators and / or cure retarders and / or stabilizers and / or dyes and / or pigments to the rubber mixture, without being limited to the listed examples. Adding the additive comprising carbon nanotubes to the rubber compound can be carried out by any known method of mixing rubber mixtures, including but not limited to internal mixers with various geometries of chambers and rotors, open mills (two roll mills or rubber mixing rolls), twin screw mixers, extruders, etc., as well as in a two-stage or multi-stage process using various combinations of mixing methods. In certain applications, the preferred process for making rubber involves adding the additives to the rubber compound in an internal mixer. In certain other applications, the preferred process for making rubber involves adding the additives to the rubber compound in a two-roll rubber mill. Mixing can be done at higher temperatures. After mixing and forming into the appropriate shape, the rubber compound can be cured by one of the known methods to make rubber.

[0040] The present invention also provides a rubber comprising nanotubes, having enhanced electrical conductivity and physical and mechanical properties, the rubber comprising 0.01 to 1% by weight of carbon nanotubes and produced by any of the processes defined above using the additive comprising carbon nanotubes as defined above.

[0041] The present invention is illustrated by the following examples and tables, which are provided for a better understanding of the nature of the invention, but the invention is not limited by the examples provided.

[0042] Brief explanation of the table Table 1 shows the components of the additives of Examples 1 to 34, the characteristics of the TUBALL® single-walled carbon nanotubes (SWCNTs) used in their production, the characteristics of the dispersion medium and high viscosity rubber used in their production, and the ratio of the mass fraction of the carbon nanotubes to the mass fraction of the rubber attached thereto.

[0043] Table 2 shows data on the viscosity and conductivity of the additives of Examples 1-34.

[0044] Table 3 shows the components of the additives in Examples 35 to 41 and the properties of the carbon nanotubes used in their production.

[0045] Table 4 shows the components of the additives in Examples 42-45.

[0046] Table 5 shows the components of the rubber compound of Example 46 based on EPDM rubber without carbon black using the additives of Examples 5-9, and the properties of the cured rubber.

[0047] Table 6 shows the components of the rubber compound of Example 46 based on EPDM rubber without carbon black using the additives of Examples 10-14, and the properties of the cured rubber.

[0048] Table 7 shows the components of the rubber compound of Example 46 based on EPDM rubber without carbon black using the additive of Example 9, and the properties of the cured rubber.

[0049] Table 8 shows the rubber compound components of Example 47 based on EPDM rubber without carbon black using the additives of Examples 35-38, and the properties of the cured rubber.

[0050] Table 9 shows the components of the rubber compound of Example 48 based on EPDM rubber containing carbon black N550, conductive filler, or conductive carbon powder Vulcan XC-72, using the additive of Example 9.

[0051] Table 10 shows the rubber compound components of Example 49 based on a colored (non-black) conductive rubber mixture based on EPDM rubber using the additives of Example 9 and Example 42, and the properties of the rubber after curing.

[0052] Table 11 shows the components of the rubber compound of Example 50 based on a mixture of natural rubber and butadiene rubber using the additives of Examples 9, 15-17 and 43-44, and the properties of the cured rubber.

[0053] Table 12 shows the components of the rubber compound of Example 51 based on a mixture of natural rubber and butadiene rubber without oil plasticizers, using the additives of Examples 16, 17 and 25, and the properties of the rubber after curing.

[0054] Table 13 shows the components of the rubber compound of Example 52 based on nitrile butadiene rubber filled with carbon black, using the additives of Examples 18-20, 25-26 and 44, and the properties of the cured rubber.

[0055] Table 14 shows the components of the rubber compound of Example 53 based on nitrile butadiene rubber filled with silicon dioxide and the properties of the cured rubber using the additives of Examples 21-23, 25, 29, and 31.

[0056] Table 15 shows the components and cured rubber properties of the rubber compound of Example 53 based on nitrile butadiene rubber filled with silicon dioxide using the additives of Examples 32-34 and 39-41.

[0057] Table 16 shows the components of the rubber compound of Example 54 based on a mixture of styrene butadiene rubber and butadiene rubber using the additives of Examples 9, 22 and 26-28, and the properties of the cured rubber.

[0058] Table 17 shows the components of the rubber compound of Example 54 based on a mixture of styrene butadiene rubber and butadiene rubber using the additives of Examples 24, 25 and 45, and the properties of the cured rubber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0059] Reference will now be made in detail to the preferred embodiments of the present invention. EXAMPLES

[0060] In the examples and tables below, the values ​​of the physical and chemical properties were experimentally determined according to the methods described in the following standards: Russian GOST R 54552-2011 Rubbers and Rubber Compounds. Standard Test Methods for Viscosity, Stress Relaxation, and Pre-Vulcanization Characteristics by Mooney Viscometer (and ASTM D 1646-2015); Russian GOST R 54547-2011 Rubber Compounds. Standard Test Method for Property-Vulcanization Using Rotorless Cure Meters (and ASTM D 5289-2012); Russian GOST R 54553-2011 Vulcanized Rubber and Thermoplastic Elastomers. Standard Test Method for Tensile Stress-Strain Properties (and ASTM D 412); Russian GOST 262-79 Rubber. Standard Test Method of Tear Strength (and ASTM D 624);Russian GOST R ISO 7619-1-2009 Rubber,Vulcanized or Thermoplastic.Determination of Indentation Hardness.Part 1.Durometer Method(Shore Hardness)(and ISO 7619-1:2004);ASTM D 991-Standard Test Method for Rubber Property-Volume Resistivity Of Electrically Conductive and Antistatic Products;Russian GOST-11501-78 Petroleum Bitumens.Standard Test Method for Determination of Depth of Needle Penetration (and DIN EN1426:2015, ASTM D 5).

[0061] The following symbols and abbreviations are used in the table below: NPD - needle penetration depth (according to Russian GOST-11501-78), expressed in penetration units equal to 0.1 mm, ρ V -Volume resistivity, ρ S - surface resistivity, M50 - stress at a given elongation of 50%, M100 - stress at a given elongation of 100%, M200 - stress at a given elongation of 200%, M300 - stress at a given elongation of 300%, TS - maximum tear stress, EB - maximum elongation at break, CrTear - tear resistance of crescent shaped sample, AnTear - tear resistance of angle shaped sample, H - hardness, λ - thermal conductivity.

[0062] Examples 1 to 34. Examples 1-4 show prototype comparative examples, i.e. additives comprising single-walled carbon nanotubes and a carrier medium which is a low molecular weight solvent with an average molecular weight of less than 1000 Daltons (aromatic oil TDAE Norman 346: a hydrogenated extract of aromatic hydrocarbons of gasoline origin with a viscosity of about 0.02 Pa·s at 100° C. and a flash point of 220° C.) or a liquid rubber oligomer (butadiene Kuraray LBR-352 with MW=9000 Da: a liquid with a viscosity of 6 Pa·s at 38° C., nitrile butadiene Nipol 1312 (Zeon Chemicals): a liquid with a viscosity of 20-30 Pa·s, or styrene butadiene-Kuraray LSBR-820 with MW=8500 g / mol: a liquid with a viscosity of 350 Pa·s at 38° C.). The composition of these additives, the properties of the TUBALL™ single-walled carbon nanotubes (SWCNTs) used in their preparation, and the properties of the dispersion medium (or liquid rubber oligomer) are shown in Table 1.

[0063] Examples 5 to 34 illustrate the additive of the present invention for improving the electrical conductivity and physical and mechanical properties of rubber containing carbon nanotubes, the additive comprising 1 to 20% by weight of carbon nanotubes, 3 to 90% of a high viscosity organic rubber (R), and 8 to 95% by weight of a low molecular weight organic dispersion medium capable of dissolving the high viscosity organic rubber (R). In each of the provided examples, the additive comprises carbon nanotubes having an average diameter (d) of more than 1.4 nm and less than 1.8 nm, a molecular weight of 300 mm or less, and a viscosity of 1.0 to 1.5 nm. 2 / g over 600m 2 The TUBALL™ single-walled carbon nanotubes have a specific surface area (S) of less than 100 nm / g, and an intensity ratio of the G / D bands in the Raman spectrum at 532 nm of greater than 40. The TUBALL™ single-walled carbon nanotubes contain iron impurities in the form of nanoparticles of iron, iron carbide, and small amounts of iron oxide.

[0064] TUBALL(trademark)(m Fe The content of iron impurities in the 1230 mm diameter tube is less than 15% by weight. The exceptions are Examples 15 and 24, which use TUBALL® single-walled carbon nanotubes that have been further purified from iron impurities to a content of 0.65% by weight. These single-walled carbon nanotubes are 1230 mm diameter tubes. 2 The additive is characterized by a larger specific surface area of ​​100 / g, which is due to the opening of the internal channels of the carbon nanotubes during the purification process. The actual values ​​of the parameters of TUBALL™ single-walled carbon nanotubes in the additive are shown in Table 1. In each example provided, the additive includes a low molecular weight carrier and a high viscosity organic rubber. The chemical composition, viscosity (η), flash point (t fl ) are shown in Table 1. The table uses the following abbreviations: TDAE - processed distillate aromatic extract, aromatic oil produced by hydrogenation of gasoline distillate, Norman 346 oil was used (JSC Orgkhim), P460 - paraffin oil type Petronas Process Oil P 460 (Petronas), DBP - dibutyl phthalate, PC - propylene carbonate, BC - butylene carbonate, DOA - dioctyl adipate, DOS - dioctyl sebacate, DINP - diisononyl phthalate.

[0065] Each additive (ML (1+4) The chemical composition, brand and viscosity in Mooney units of the high viscosity organic rubbers used in the 2006-2010 CE 2007-01 CE 2008-01 CE 2009-02 CE 2010-03 CE 2020 are shown in Table 1. The table uses the following abbreviations: NR - natural rubber, NBR - nitrile butadiene rubber, EPDM - ethylene propylene diene monomer rubber. Table 1 also shows the weight percent ratio of the weight of TUBALL™ to the weight of additive (m CNT ), the weight percentage ratio of the weight of the high viscosity organic rubber (R) to the weight of the rubber (R) solution in the dispersion medium (m R ), and the ratio of the weight of SWCNTs to the weight of rubber attached to them (m CNT / BdR ) is shown.

[0066] The additives of Examples 5-34 were prepared by sequentially performing step (I) of dissolving the high viscosity organic rubber (R) in a dispersion medium, followed by step (II) of dispersing the single-walled carbon nanotubes in the solution of step (I). To prevent dust formation in the working area during dispersion, the single-walled carbon nanotubes were pre-wetted between steps (I) and (II) with the dispersion medium (oil P460) in Examples 5-14 and with the rubber solution in the dispersion medium in Examples 15-34.

[0067] The dispersion medium in the additives of Examples 5-16 includes a mineral oil having a flash point above 200°C and a viscosity below 0.1 St at 100°C (21 cSt for TDAE Normal 346 and 36 cSt for Petronas P460). The dispersion medium in the additives of Examples 18-31 includes a nitrile butadiene rubber and a polar solvent having a relative dielectric constant above 5 at 25°C (DBP: 6.4; butylene carbonate: 56; propylene carbonate: 64). In Example 30, the dispersion medium is solution 1 of propylene carbonate and butylene carbonate in a weight ratio of 9:1 (the isomer composition of the butylene carbonate is unknown). In Example 31, the dispersion medium is solution 2 of propylene carbonate and butylene carbonate in a weight ratio of 1:9 (the isomer composition of the butylene carbonate is unknown). The dispersion medium in the additives of Examples 32 to 34 contains a polar solvent having a lower relative dielectric constant (DOS: 4.0; DINP: 4.6).

[0068] Table 2 shows data on the viscosity and conductivity at a temperature of 25° C. for the additives of Examples 1 to 34.

[0069] Examples 35 to 41. The additives of Examples 35-38 were prepared similarly to the additive of Example 9, and the additives of Examples 39-41 were prepared similarly to Example 26, but with different carbon nanotubes having the properties shown in Table 3. Examples 35 and 39 used carbon nanotubes containing mostly double-walled carbon nanotubes, as confirmed by high resolution transmission electron microscopy, with a mass fraction of single-walled carbon nanotubes of about 30 wt%. Examples 36, 37 and 40 used multi-walled carbon nanotubes, but in Example 37 they were premixed with TUBALL™ single-walled carbon nanotubes in a 3:1 weight ratio. Examples 38 and 41 used so-called "few-walled" carbon nanotubes, i.e. multi-walled carbon nanotubes with the number of graphene layers in the wall between 2 and 5, and the carbon nanotubes mostly contained 3 to 4 graphene layers.

[0070] Examples 42 to 45. The additives were prepared similarly to the additives of Examples 9, 17 and 26, but after step (II) there was a further step of mixing the resulting slurry comprising carbon nanotubes, carrier fluid and high-viscosity organic rubber (R) with high-viscosity organic rubber (R2) in a ratio of the weight of rubber (R2) to the weight of the slurry after step (II) not more than 5. The composition and type of rubber (R2) used, the weight ratio of the weight of rubber (R2) to the weight of the slurry after step (II), as well as the final composition of the additive and the weight ratio of carbon nanotubes to bound rubber are shown in Table 4.

[0071] Example 46. This example shows the preparation of rubber mixtures and rubbers based on EPDM rubber without carbon black using the additives of Examples 5 to 14. The additive of Comparative Example 2 was used for comparison with the prototype. The rubber was mixed in two stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill 200 / 400 with a diameter of 200 mm, a length of 400 mm, and a friction coefficient of 1:1.2. In the first stage, the rubber, oil P460, PEG4000, CaCO3, white carbon (SiO2), kaolin, TiO2, and ZnO are mixed for 5 minutes at a maximum mixing temperature of 150 ° C. In the second stage, the curing agents of triallyl isocyanurate (TAIC) and bis(tert-butylperoxyisopropyl)benzene (BIPB-40-GR), as well as additives including carbon nanotubes, are introduced into the rubber compound for 2 minutes at a maximum mixing temperature of 90 ° C. Rubber mixing includes adding an additive, including carbon nanotubes, to a rubber compound, the addition of the additive to the rubber compound being combined with the addition of a curative to the rubber compound.

[0072] The rubber mixture formulations and the results of testing the cured rubber samples for electrical conductivity as well as physical and mechanical properties are shown in Tables 5 and 6. These data show that the additives of Examples 5-14 provide technical results, i.e. significantly improved electrical conductivity and mechanical properties (modulus M50-M200 and tear resistance), while the effect of the additive of Comparative Example 2 on electrical conductivity and tear resistance is much lower and is actually negative for M50-M200.

[0073] The effect of the amount of additive introduced is shown by Table 7, which gives data for various amounts of additive of Example 9. Varying the concentration of carbon nanotubes in the rubber from 0.04 to 1% results in technical results: significantly improved electrical conductivity and mechanical properties (modulus M50-M200 and tear resistance) are achieved, some rubber samples also show significantly increased tensile strength and maximum elongation at break.

[0074] Example 47. This example shows the preparation of rubber mixtures and rubbers based on EPDM rubber without carbon black using the additives of Examples 35 to 38. The additive of Comparative Example 2 was used for comparison with the prototype. The rubber was mixed in two stages using an internal mixer WSM SKI-3.5L as in Example 48 and homogenized after mixing on a two-roll rubber mill Zamak LM 200 / 400 with a diameter of 200 mm, a length of 400 mm and a friction coefficient of 1:1.2.

[0075] The rubber mix formulations and the results of testing the cured rubber samples for electrical conductivity as well as physical and mechanical properties are shown in Table 8. These data show that the additives of Examples 35-38 provide technical results, i.e. improved electrical conductivity and mechanical properties (modulus M50-M200 and tear resistance), but the greatest effect is achieved when using single-walled and / or double-walled carbon nanotubes (additives of Examples 9 and 35). Therefore, additives containing single-walled and / or double-walled carbon nanotubes are preferred.

[0076] Example 48. This example shows the preparation of rubber mixtures and rubbers based on EPDM rubber containing carbon black N550, conductive filler, or conductive carbon powder Vulcan XC-72, using the additive of Example 9. The additive of Comparative Example 2 was used for comparison with the prototype. The rubber was mixed in two stages: the first stage was carried out using an internal mixer VSM SKI-3.5L, and the second stage was carried out on a two-roll rubber mill Zamak 200 / 400 with a diameter of 200 mm, a length of 400 mm, and a friction coefficient of 1:1.2, at a maximum temperature of 90 ° C for 2 minutes. The additive containing carbon nanotubes was introduced into the two-roll rubber mill, combining the addition of this additive to the rubber compound with the addition of curatives (2-mercaptobenzothiazole (MBT), tetramethylthiuram disulfide (TMTD) and sulfur) to the rubber compound.

[0077] The formulation of the rubber mixture and the results of testing the cured rubber samples for electrical conductivity as well as physical and mechanical properties are shown in Table 9. These data show that the additive of Example 9 provides technical results, namely significantly enhanced mechanical properties (modulus M50-M200 and tear resistance), as well as a very significant increase in electrical conductivity, despite the fact that the rubber was already electrically conductive without the additive. At the same time, the effect of the additive of Comparative Example 2 on the physical and mechanical properties is significantly lower and, within the uncertainty of the measurements, the electrical conductivity of the rubber containing this additive is actually reduced.

[0078] Example 49. This example shows that further technical results can be achieved by using the additive of the invention, i.e. by producing colored (non-black) conductive rubber mixtures and rubbers based on EPDM rubber. The rubber formulation is shown in Table 10. For coloration, the organic dye phthalocyanine blue pigment was added to the rubber mixture. The titanium dioxide content was increased to whiten the rubber. This example also shows the possibility of adding carbon nanotubes to rubber mixtures as part of an additive with a high concentration of high-viscosity organic rubber according to Example 42. The base rubber without additives was mixed in two stages: in the first stage, which was carried out using an internal mixer VSM SKI-3.5L, all components were added to the rubber except the curing system (TAIC and peroxide). The second stage, which included the addition of the curatives, was carried out using a two-roll rubber mill Zamak 200 / 400 with a diameter of 200 mm, a length of 400 mm and a coefficient of friction of 1:1.2, at a maximum temperature of 90 ° C for 2 minutes. The additives including the carbon nanotubes were introduced into the rubber using an internal mixer before adding the other components of the rubber mixture. The resulting rubber has a deep blue color with sufficient conductive properties to dissipate static charge. The data in Table 10 demonstrate that the addition of both the additives of Example 9 and Example 42 resulted in improved physical and mechanical properties of the rubber.

[0079] Example 50. This example shows the preparation of rubber compounds and rubbers based on a mixture of rubbers, namely natural rubber (SMR10 rubber was used) and butadiene rubber (BR-22 rubber was used) using any of the additives of Examples 9, 15-17 and 43-44. The additive of Comparative Example 1 was used for comparison with the prototype. The composition of the rubber mixture is shown in Table 11. This composition emulates the composition of the rubber mixture in the treads of agricultural and truck tires. The rubber without additives was mixed in two stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill Zamak 200 / 400 with a friction coefficient of 1:1.2. In the first stage, the rubber, oil Nytex 4700, carbon black N234, stearic acid, ZnO, N-(1,3-dimethyl)-N'-phenyl-1,4-phenyldiamine (6PPD) antioxidant were mixed for 5 minutes at a maximum mixing temperature of 130 ° C. In the second stage, the curatives 2,2,4-trimethyl-1,2-dihydroquinoline (TMQ); N-cyclohexyl-2-benzothiazole sulfenamide (sulsenamide C) (CBS); diphenyl guanidine (DPG), pre-vulcanization inhibitor (PVI), and sulfur were introduced into the rubber compound for 2 minutes at a maximum mixing temperature of 100°C. The stage of adding additives containing carbon nanotubes was carried out between the first and second stages of mixing the base rubber mixture using a two-roll rubber mill Zamak 200 / 400 with a friction coefficient of 1:1.2. The volume resistivity of the cured rubber samples as well as their physical and mechanical properties are shown in Table 11, and pre-cut crescent-shaped samples were used for the tear resistance test. These data show that the addition of the additives of Examples 15-17, 43, 9 and 42 to the rubber compounds significantly reduces the volume resistivity of the rubber and increases the stress values, tensile strength and tear resistance at a given elongation of 100-300%, but does not adversely affect the maximum elongation at break. At the same time, the addition of the additive of Comparative Example 1, shown here for comparison with the prototype, does not result in any significant improvement of the rubber properties.

[0080] Example 51. This example shows the preparation of rubber mixtures and rubbers based on a mixture of rubbers, namely natural rubber (SVR-3L rubber was used) and butadiene rubber (Buna CB 24 rubber was used), without the use of plasticizer oils, using any of the additives of Examples 16, 17 and 25. The additive of Comparative Example 1 was used for comparison with the prototype. The composition of the rubber mixtures is shown in Table 12. The rubber without additives was mixed in two stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill Zamak 200 / 400 with a friction coefficient of 1:1.2. In the first stage, rubber, carbon black N330, stearic acid, ZnO, N-(isopropyl)-N'-phenyl-1,4-phenyldiamine (iPPD) antioxidant were mixed for 5 minutes at a maximum mixing temperature of 130°C. In the second stage, the curatives of benzothiazole sulfenamide (CBS); diphenyl guanidine (DPG) and sulfur, as well as the additives, were introduced into the rubber compound over a period of 2 minutes at a maximum temperature of 100° C. Thus, the stage of adding the additives, including carbon nanotubes, is combined with the stage of adding the curing system.

[0081] The volume resistivity of the cured rubber samples and their physical and mechanical properties are shown in Table 12, and pre-cut crescent-shaped samples were used for the tear resistance test. The addition of the additives of Examples 16, 17, and 25 to the rubber compound significantly reduces the volume resistivity of the rubber and increases the stress value at a given elongation of 100-300%, as well as the tear resistance, but does not have a significant adverse effect on the maximum breaking elongation and tensile strength. Also, the addition of the additives of Examples 16, 17, and 25 to the rubber compound improves the rubber hardness. At the same time, the addition of the additive of Comparative Example 1, shown here for comparison with the prototype, does not bring about any significant improvement in the rubber properties.

[0082] Example 52. This example shows the preparation of rubber mixtures and rubbers based on nitrile butadiene rubber filled with carbon black using the additives of Examples 18-20, 25-26 and 44. For comparison with the prototype, the additive of Comparative Example 3 was used (dispersion of single-walled carbon nanotubes in liquid nitrile butyl rubber oligomer Nipol 1213). The rubber was mixed in two stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill 200 / 400 with a diameter of 200 mm, a length of 400 mm and a friction coefficient of 1:1.2. In the first stage, the rubber, carbon black, ZnO, stearic acid, dibutyl phthalate (DBP), N-(isopropyl)-N'-phenyl-1,4-phenyldiamine (iPPD) antioxidant were mixed for 5 minutes at a maximum mixing temperature of 120 ° C. In the second stage, the vulcanizing agents N-cyclohexyl-2-benzothiazole sulfenamide (CZ) and sulfur were added over a period of 2 minutes at a maximum mixing temperature of 90° C. The stage of adding the additives including carbon nanotubes was carried out using an internal mixer. The addition of this additive to the rubber compound is combined with the addition of the vulcanizing agents to the rubber compound.

[0083] The rubber mixture formulations and the results of testing the cured rubber samples for electrical conductivity as well as physical and mechanical properties are shown in Table 13. These data show that the additives of Examples 18-20, 25-26 and 46 provide technical results, i.e. improved mechanical properties (modulus M50-M200 and tear resistance) as well as improved electrical conductivity, while the effect of the additive of Comparative Example 3 on electrical conductivity is significantly lower and there is no effect on physical and mechanical properties.

[0084] Example 53. This example shows the preparation of rubber mixtures and rubbers based on nitrile butadiene rubber filled with silicon dioxide using the additives of Examples 21-23, 25, 29, 31-34, and 39-41. For comparison with the prototype, the additive of Comparative Example 3 was used (dispersion of single-walled carbon nanotubes in liquid nitrile butyl rubber oligomer Nipol 1213). The rubber was mixed in two stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill 200 / 400 with a diameter of 200 mm, a length of 400 mm, and a friction coefficient of 1:1.2.

[0085] In the first stage, rubber, carbon black, ZnO, stearic acid, silicon dioxide, silane coupling agent TESPT (Si-69), titanium dioxide and N-(isopropyl)-N'-phenyl-1,4-phenyldiamine (iPPD) antioxidant were mixed for 5 minutes at a maximum mixing temperature of 150°C. In the second stage, the curatives of mercaptobenzothiazole disulfide (MBTS), tetramethylthiuram disulfide (TMTD) and sulfur were introduced into the rubber compound for 2 minutes at a maximum temperature of 90°C. The stage of adding additives including carbon nanotubes was carried out using an internal mixer. The addition of this additive to the rubber compound is combined with the addition of the curatives to the rubber compound.

[0086] The rubber mixture formulations and the results of testing the cured rubber samples for electrical conductivity as well as physical and mechanical properties are shown in Tables 14 and 15. These data show that the additives of Examples 21-23, 25, 29, 31-34 and 39-41 provide technical results, i.e. an improvement in the mechanical properties of the rubber (modulus M50-M200 and tear resistance) and electrical conductivity sufficient to dissipate electrostatic charges, but that larger amounts of additives 40-41 (containing multi-walled carbon nanotubes) are required to achieve the technical results, while the effect of the additive of Comparative Example 3 on electrical conductivity and tear resistance is not significant.

[0087] Example 54. This example shows the preparation of rubber mixtures and rubbers based on a mixture of rubbers, namely styrene butadiene rubber (solution SBR Buna VSL 4526-2HM swollen with TDAE oil) and butadiene rubber (Buna CB 24 rubber was used) using any of the additives of Examples 9, 22, 24-28, and 45. For comparison with the prototype, the additive of Comparative Example 4 was used, in which single-walled carbon nanotubes were dispersed in a liquid oligomer of styrene butadiene rubber Kuraray LSBR-820. The composition of the rubber mixtures is shown in Tables 16 and 17. This composition emulates the composition of rubber mixtures for treads of automobile tires. It should be noted that the rubber mixtures do not contain carbon black or any other conductive fillers apart from the additives containing carbon nanotubes. The rubbers without additives were mixed in three stages using an internal mixer WSM SKI-3.5L and homogenized after mixing on a two-roll rubber mill Zamak 200 / 400 with a friction coefficient of 1:1.2.

[0088] In the first stage, rubber, oil TDAE Normal 346, silicon dioxide, silane coupling agent bis(triethoxysilylpropyl)tetrasulfide (Si-69), and stearic acid were mixed for 5 minutes at a maximum mixing temperature of 150 °C. The amount of plasticizer (TDAE oil) was reduced by the amount of low molecular weight dispersing medium introduced with the additives. In the second stage, homogenization of the mixture was performed and zinc oxide and N-(1,3-dimethyl)-N'-phenyl-1,4-phenyldiamine (iPPD) antioxidant were added over 2 minutes at a maximum mixing temperature of 110 °C. In the third stage, sulfur, N-tert-butyl-2-benzothiazole sulfenamide (TBBS) and diphenyl guanidine (DPG) curing agents were introduced into the rubber compound over 2 minutes at a maximum mixing temperature of 110 °C. The additives were introduced in the second stage, while the stage of adding the additives was combined with homogenization of the mixture and the addition of zinc oxide and antioxidants. The exception is that the additive of Example 45 is added to the styrene butadiene rubber in a separate step on a two-roll rubber mill before step 1. The volume resistivity of the cured rubber samples and their physical and mechanical properties are shown in Tables 16 and 17, and pre-cut crescent shaped samples were used for tear resistance testing.

[0089] The data show that the addition of the additives of Examples 9, 22, 24-28 and 45 to a rubber compound significantly reduces the volume resistivity and surface resistivity of the rubber, while providing a conductive rubber in the absence of other conductive fillers, increasing the stress values ​​and tensile strength and tear resistance at a given elongation of 100-300% without detrimentally affecting the maximum elongation to break. At the same time, the addition of the additive of Comparative Example 4, shown here for comparison with the prototype, does not result in any significant improvement in the rubber properties.

[0090] As shown in Table 17, the addition of the additives of Examples 24-25 and 45 significantly increases the loss tangent (tan(δ)) in the dynamic mechanical test at 0°C, which characterizes the friction coefficient and traction of the tire tread. Thus, adding the additives to the rubber mixture for the manufacture of tire treads can significantly improve tire quality. It should be noted that this addition of the additives has a very small effect on (tan(δ)) at high temperatures (such as 60°C), i.e. it does not increase the rolling resistance of the tire.

[0091] It should also be noted that this example further illustrates that the addition of 0.38 wt.% carbon nanotubes achieves an additional technological effect, namely a 10% increase in thermal conductivity of the cured rubber. Thermal conductivity data is shown in Table 17. [Table 1] JPEG2024510922000002.jpg254122JPEG2024510922000003.jpg254122 [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7] [Table 8] [Table 9] [Table 10] [Table 11] [Table 12] [Table 13] [Table 14] [Table 15] [Table 16] [Table 17] [Industrial Applicability]

[0092] The present invention can be used in the manufacture of rubber compounds to provide rubbers with improved electrical conductivity and physical and mechanical properties.

Claims

1. 1. An additive to a rubber compound for improving the electrical conductivity and physical and mechanical properties of the rubber, comprising: 1-20% by weight of carbon nanotubes; 3 to 90% by weight of a high viscosity organic rubber; and 8 to 95% by weight of a low-molecular-weight organic dispersion medium capable of dissolving the high-viscosity organic rubber (R), (a) an oil having a flash point greater than 200°C and a kinematic viscosity at 100°C of less than 1 St; (b) a polar solvent having a dielectric constant greater than 5 at 25°C; and (c) an additive selected from the group consisting of an ester or a mixture of one or more esters of an aliphatic alcohol and an acid selected from the group consisting of (1) phthalic acid, (2) terephthalic acid, (3) sebacic acid, (4) adipic acid, and (5) cyclohexanedicarboxylic acid.

2. 2. The additive of claim 1, wherein the high viscosity organic rubber is selected from the group consisting of natural rubber, synthetic isoprene rubber, styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, butadiene or butyl rubber, halobutyl rubber, ethylene propylene rubber, ethylene propylene diene rubber containing ethylene norbornene or dicyclopentadiene as a third monomer, propylene oxide rubber, acrylate rubber, carboxylate rubber, chloroprene rubber, fluoroelastomers, and mixtures of two or more of these rubbers.

3. The high viscosity organic rubber has a viscosity ML of greater than 20 Mooney units at 100° C. (1+4) The additive of claim 1 having the formula:

4. The high viscosity organic rubber has a viscosity ML of greater than 40 Mooney units at 100° C. (1+4) The additive of claim 3 having the formula:

5. The high viscosity organic rubber has a viscosity ML of greater than 60 Mooney units at 100° C. (1+4) The additive of claim 4 having the formula:

6. 2. The additive of claim 1, wherein the carrier fluid is a polar solvent having a dielectric constant greater than 40 at 25°C.

7. 7. The additive of claim 6, wherein the carrier fluid comprises at least 10% by weight propylene carbonate.

8. The additive of claim 6, wherein the carrier fluid comprises at least 10% by weight of 1,2-butylene carbonate, or 2,3-butylene carbonate, or a mixture thereof.

9. 2. The additive of claim 1, wherein greater than 25% by weight of the carbon nanotubes are single-walled or double-walled carbon nanotubes.

10. 2. The additive of claim 1, wherein the carbon nanotubes have an intensity ratio of the G / D bands greater than 10 in a Raman spectrum at 532 nm.

11. 11. The additive of claim 10, wherein the carbon nanotubes have an intensity ratio of the G / D band in a Raman spectrum at 532 nm of greater than 40.

12. 11. The additive of claim 10, wherein the carbon nanotubes have an intensity ratio of the G / D band in a Raman spectrum at 532 nm of greater than 60.

13. 2. The additive of claim 1, wherein the ratio of the mass fraction of the carbon nanotubes to the mass fraction of the rubber attached to the carbon nanotubes is less than 4.

14. The additive of claim 1 , wherein at least a portion of the carbon nanotubes are bundled.

15. 15. The additive of claim 14, wherein at least a portion of the carbon nanotube bundles have a thickness greater than 300 nm.

16. 10. The additive of claim 1 further comprising particles of one or more metals from Groups 8 to 11 or alloys thereof.

17. 10. The additive of claim 1, wherein the additive has a volume resistivity of less than or equal to 2 ohm-m at a temperature of 25°C.

18. 2. The additive of claim 1, wherein the additive has a viscosity of greater than 5 and less than 90 Mooney units at a temperature of 100°C.

19. 10. The additive of claim 1, wherein the viscosity of the additive is characterized by a needle penetration depth of less than 15 mm at a temperature of 25°C under a specified load of 100 g for 5 seconds.

20. 2. A method for the preparation of the additive of claim 1, comprising the following sequential steps: (I) dissolving said high viscosity rubber (R) in said dispersion medium; and (II) dispersing carbon nanotubes in the solution of step (I).

21. 21. The method according to claim 20, further comprising an additional step between step (I) and step (II) of pre-wetting and mixing carbon nanotubes in the dispersion medium or one of its components, or in a solution of rubber (R) in the dispersion medium.

22. 22. The method of claim 21, further comprising a step (III) of mixing the resulting slurry of carbon nanotubes, the dispersion medium and the high-viscosity organic rubber (R) with a high-viscosity organic rubber (R2) after step (II), wherein the ratio of the weight of the rubber (R2) to the weight of the slurry after step (II) is 5 or less.

23. A method of making rubber comprising adding the additive of claim 1 to said rubber.

24. 24. The method of claim 23, wherein said doping further comprises adding fillers, and / or plasticizers, and / or antioxidants, and / or silane coupling agents, and / or curing agents, and / or cure accelerators, and / or cure retarders, and / or stabilizers, and / or dyes, and / or pigments to the rubber.

25. 24. The method of claim 23, wherein the adding is performed using an internal mixer.

26. 24. The method of claim 23, wherein said adding is carried out using a two-roll rubber mill.

27. A rubber having improved electrical conductivity and physical and mechanical properties, comprising 0.01 to 1 weight percent carbon nanotubes and produced by the method of claim 23.